2010
DOI: 10.1002/pip.982
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency inline diffused emitter (ILDE) solar cells on mono‐crystalline CZ silicon

Abstract: High throughput, low cost, and high efficiency are the keys to reducing the cost of photovoltaic electricity. To realize high efficiency, the quality of emitter is critical. The emitter can be formed either by batch deposition in a tube using liquid POCl 3 source or by inline spray deposition of phosphoric acid (P 2 O 5 ). The POCl 3 process has been optimized over the years to give reproducible performance, whereas the inline diffusion has not been systematically optimized. This paper reports on solar cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Ebong et al observed an increase in phosphorus emitter sheet resistance and decrease in surface doping concentration after an HF dip, which indicated that considerable amount of Si was removed in the solution [15]. Liu et al studied the topic further and discovered that phosphorus concentration affects the etch rate of Si in HF.…”
mentioning
confidence: 99%
“…Ebong et al observed an increase in phosphorus emitter sheet resistance and decrease in surface doping concentration after an HF dip, which indicated that considerable amount of Si was removed in the solution [15]. Liu et al studied the topic further and discovered that phosphorus concentration affects the etch rate of Si in HF.…”
mentioning
confidence: 99%
“…An absolute efficiency gain of 0.2-0.3% with a moderate increase in emitter R sq (i.e., ΔR sq ) of 6 Ω/sq was reported when using this 'surface clean' [11]. Ebong et al [3] reported an 'extended surface clean' process and achieved an average efficiency of 17.4% for ILDE mono-Si wafer cells. Using an inline diffusion furnace with ceramic rollers and 'augmented clean' emitter etch-back process, Rousenville et al [12] reported a champion efficiency of 18.2% for mono-Si solar cells featuring a plated Ag front metallization (using a screen-printed Ag seed layer).…”
Section: Introductionmentioning
confidence: 95%
“…As a result, processing conditions must be chosen to address these impacts, otherwise typical cell efficiency of an inline-diffused emitter (ILDE) Si solar cells can be lower compared to their tube-diffused counterpart. A surface 'dead layer' can be formed on the ILDE surface by a high dopant concentration at the surface and surface contaminants resulting from direct deposition of dopants on the wafers [2,3]. This dead layer directly limits short-circuit current (I sc ) and open-circuit voltage (V oc ) of the solar cell [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations